Effect of Acute Acai (Euterpe oleracea Mart.) Supplementation on Postprandial Glycaemia in Healthy Adults: A Pilot Randomised Controlled Study. (7th June 2021) - Myrissa, Kyriaki; Chappell, Paul; Kelaiditi, Eirini
Abstract: Objectives: Anthocyanin rich foods may ameliorate postprandial glycaemia. Postprandial glycaemia is associated with Type 2 Diabetes and a risk factor for cardiovascular disease. Acai berry is high in anthocyanins and has received attention for its health benefits. However, human trials are limited. The objective of the present study was to investigate the effect of acai berry extract on postprandial glycaemia responses in healthy adults. Methods: Ten healthy participants, aged 18–65 years (mean 33 ± 16), with a body mass index (BMI) of 18.5–24.9 kg/m 2 (mean 22.2 ± 1.5) completed a randomized, controlled, double-blind, crossover, acute dietary intervention trial. Participants consumed either an acai-based smoothie (AS) containing 150g acai pulp or a macronutrient-matched control placebo smoothie (PS). The primary endpoint was blood glucose concentration (BGC) which was determined by a capillary sampling method at baseline and at regular intervals up to 2 hours postprandially. Results: Consumption of acai resulted in lower mean BGC compared to placebo (5.38 ± 0.46mmol/l vs. 5.40 ± 0.63mmol/l), but this was not significant (p = 0.888), even after controlling for age and BMI. There was no significant difference in BGC incremental area under the curve (iAUC) for acai relative to placebo. Conclusions: In this acute study on heathy adults of a wide age range, acai consumption was not associated with improvements in postprandial glycaemia. Future long-term, adequately powered intervention studies, assessing additional biomarkers of disease risk are needed to fully elucidate the benefits of acai to health. Funding Sources: None.